A new derivation of the conformally flat stationary cyclic non-circular spacetimes - Ayón Beato, Eloy (2007)
We present an alternative way to derive the conformally flat stationary cyclic non-circular spacetimes. We show that there is no room for stationary axisymmetric non-circular axisymmetric spacetimes. We reproduce the well know results for this sort of spacetimes recently reported in [1].